PELATIHAN PEMBUATAN BAHAN AJAR DAN ASESMEN DIGITAL BERBASIS BUDAYA JAMBI BERBANTUAN AI-AR - Husni Sabil; Nizlel Huda; Masyunita Siregar; Novferma Novferma (Jurnal Pengabdian Masyarakat Khatulistiwa, 2025)
ABSTRACTThe digital transformation in education requires teachers to possess strong digital literacy and the ability to integrate technology with local culture to create meaningful learning experiences. This community service aimed to enhance teachers’ competence in developing digital teaching materials and assessments based on Jambi culture assisted by Artificial Intelligence (AI) and Augmented Reality (AR). The training was conducted using a participatory empowerment approach combined with a Project-Based Learning (PBL) model through four stages: socialization, hands-on workshop, implementation, and mentoring. Twenty teachers of the Junior High School Mathematics Teacher Working Group (MGMP) in Muaro Jambi participated in the program. Data were collected through observation, pre–post tests, interviews, and document analysis. The results showed a significant improvement in teachers’ competence, with the average score increasing from 63.2 to 88.5 (g = 0.68, high category). Teachers successfully produced interactive digital teaching materials that integrate Jambi’s cultural values using AI–AR tools such as Canva AI, ChatGPT, and Assemblr EDU. The program contributed to the development of the Techno-Cultural Pedagogy model, which integrates technology, pedagogy, and cultural knowledge to support digital transformation in education.Keywords: Digital Literacy, AI–AR, Teacher Training, Jambi CultureABSTRAKTransformasi digital dalam dunia pendidikan menuntut guru memiliki literasi digital yang kuat serta kemampuan mengintegrasikan teknologi dengan budaya lokal untuk menciptakan pembelajaran yang bermakna. Kegiatan pengabdian ini bertujuan meningkatkan kompetensi guru dalam mengembangkan bahan ajar dan asesmen digital berbasis budaya Jambi berbantuan Artificial Intelligence (AI) dan Augmented Reality (AR). Pelatihan dilaksanakan dengan pendekatan participatory empowerment dan model Project-Based Learning (PBL) melalui empat tahap, yaitu sosialisasi, pelatihan praktik, implementasi, serta pendampingan. Peserta kegiatan terdiri atas 20 guru MGMP Matematika SMP Kabupaten Muaro Jambi. Data dikumpulkan melalui observasi, tes pre–post, wawancara, dan analisis dokumen. Hasil menunjukkan peningkatan signifikan pada kompetensi guru dengan rata-rata skor meningkat dari 63,2 menjadi 88,5 (g = 0,68; kategori tinggi). Guru berhasil menghasilkan bahan ajar digital interaktif yang mengintegrasikan nilai budaya Jambi dengan dukungan aplikasi AI–AR seperti Canva AI, ChatGPT, dan Assemblr EDU. Kegiatan ini berkontribusi pada pengembangan model Techno-Cultural Pedagogy yang memadukan teknologi, pedagogi, dan budaya untuk mendukung transformasi digital pendidikan.Kata Kunci : Literasi Digital, AI–AR, Pelatihan Guru, Budaya Jambi